Therapy of psoriasis with narrowband ultraviolet-B light influences plasma concentrations of MMP-2 and TIMP-2 in patients - Głażewska EK; Niczyporuk M; Ławicki S; Szmitkowski M; Zajkowska M; Będkowska GE; Przylipiak A (Dove Medical Press, 2016)
Edyta Katarzyna Głażewska,1 Marek Niczyporuk,1 Sławomir Ławicki,2 Maciej Szmitkowski,2 Monika Zajkowska,2 Grażyna Ewa Będkowska,3 Andrzej Przylipiak1 1Department of Esthetic Medicine, 2Department of Biochemical Diagnostics, 3Department of Haematological Diagnostics, Medical University, Białystok, Poland Background: Matrix metalloproteinases (MMPs), which show a significant ability to cleave the components of extracellular matrix, and tissue inhibitors of metalloproteinases (TIMPs), which slow down the activity of those enzymes, may be implicated in the pathogenesis and spread of psoriatic disease. This study aims to analyze plasma levels of MMP-2 and TIMP-2 in plaque psoriasis patients before and after the course of narrowband ultraviolet-B (NBUVB) therapy with respect to disease advancement. Patients and methods: A total of 49 patients suffering from plaque psoriasis and 40 healthy volunteers were enrolled into the study. Plasma levels of MMP-2 and TIMP-2 were determined using enzyme-linked immunosorbent assay, while Psoriasis Area and Severity Index (PASI) was used to define the disease advancement. Results: The results showed increased plasma levels of MMP-2 and TIMP-2, but this change was significant only in case of MMP-2 in total psoriatic group compared to healthy subjects. Moreover, there was an increase in the concentrations of chosen factors with an increase in the severity of the disease. The NBUVB therapy causes a decline in the concentration of the analyzed enzyme and its inhibitor, although this change was statistically significant in the total psoriatic group only in case of MMP-2. There was also a positive correlation between MMP-2, TIMP-2, and PASI score value. Conclusion: Our study highlights a possible important role of MMP-2 in the activity of psoriasis and clearance of disease symptoms. Moreover, plasma MMP-2 seems to be a valuable psoriasis biomarker. Keywords: gelatinase A, matrix metalloproteinases, tissue inhibitor of metalloproteinases, NBUVB therapy